Smart City Planning To Create Good And Clean Government In Ternate City - Guret, Rahmat; Albaar, Muhammad Ridha; Samad, Abjan (Akademi Ilmu Komputer Ternate, 2024)
Abstract: In the journey towards a Smart City, efforts to make it a bridge that connects people's expectations of appropriate, effective, and efficient government services by utilizing Information and Communication Technology (ICT) is of the essence. The Smart Governance concept is the main key, where the Ternate City Government as executor of government duties is expected to be able to provide quality services following Standard Operating Procedures (SOP) and the principles of law, humanity, justice, democracy, participation, transparency, accountability, and commitment to the welfare of its citizens. To realize the Smart City vision in Ternate, there needs to be a mutual understanding regarding the true Smart City paradigm.